ANALYSIS OF COOPERATIVE PRINCIPLES IN THE MAIN CHARACTER OF THE FILM BRIDGE TO TERABITHIA - Nenni Triana Sinaga; Renatha Samanta Br Samosir; Kammer Tuahman Sipayung (J-Shelves of Indragiri (JSI), 2024)
The cooperative principle is a term used in conversation to provide information to the speaker and listener. This research aims to analyze the types of cooperative principles and find out the most dominant types of maxims of cooperative principles on the main character in the film "Bridge to Terabithia". This research uses the Descriptive Qualitative method by selecting and collecting data from the film Bridge to Terabithia. After selecting and collecting the data, the researcher identified and analyzed the utterances in the conversation between the main characters using Grice's (1975) theory related to the study of pragmatics. The results show that (1) the Cooperation Principle is categorized in the data of Maxim of Quantity 7, Maxim of Quality 10, Maxim of Relation 13, and Maxim of Manner 3; (2) the percentage of types of Cooperation Principle is the Maxim of Quantity 21,21%, Maxim of Quality 30,30% Maxim of Relations 39.39%, and Maxim of Manner 9.10%. The most dominant type of Cooperative Principle used between the main characters in the film Bridge to Terabithia is the Maxim of Relation 39,39%. In conclusion, based on this research, communication between speakers and listeners is expected to make contributions that are relevant to the topic being discussed and stay focused on the subject matter.